Making complementary agricultural resources, technologies, and services more gender-responsive - Hidrobo, Melissa; Kosec, Katrina; Gartaula, Hom N.; Van Campenhout, Bjorn; Carrillo, Lucia (Elsevier, 2024)
Rural women in low- and middle-income countries face multiple constraints in accessing and benefiting from essential complementary resources, technologies, and services for agricultural production and participation in the agrifood system. This paper highlights recent thinking around these constraints and how to overcome them. The complementary factors we consider are: (1) networks and social capital, (2) information and communications technologies, (3) other agricultural tech nologies, (4) agricultural extension and advisory services, (5) financial services, and (6) social assistance. We first analyze constraints women face in accessing and benefiting from these complementary factors and describe the potential benefits of reducing these constraints and gender inequities in the agrifood system. We then provide evidence on what has been effective for improving women’s access to and ability to benefit from the six complementary factors. We conclude by highlighting the importance of considering the different preferences of men and women when designing policies and interventions; challenging customs, norms and perceptions; and reforming formal rules and institutions toward more inclusive agrifood systems.